The Effect Of Stocking Density On The Growth Of Sangkuriang Catfish (Clarias gariepinus) In The Bucket Fish Cultivation System (BUDIKDAMBER) - Muhamad Diaz Ilyasa; Yuli Andriani; Zahidah Zahidah; Ujang Subhan (Jurnal Media Akuakultur Indonesia, 2025)
Sangkuriang catfish (Clarias gariepinus) is one of the most commonly cultivated freshwater fish species in Indonesia. The high production of catfish is largely due to the efforts of fish farmers who are able to produce sufficient quantities to meet the increasing consumption demand. One of the aquaculture methods used is the BUDIKDAMBER system, which involves fish farming in buckets with high stocking densities. This study employed an experimental method using a Completely Randomized Design (CRD) consisting of 3 stocking density treatments with 4 replications: A (1 fish/liter), B (2 fish/liter), and C (3 fish/liter) for a period of 30 days. The fish were kept in buckets prepared for the budikdamber activity, with stocking densities adjusted according to each treatment, and were fed three times a day. Water quality was monitored every 3 days. The results of the study showed that up to a density of 3 fish/liter of Sangkuriang catfish fingerlings, there was no significant difference among the different stocking density treatments, and all treatments still demonstrated good performance. The best treatment was found in treatment C (3 fish/liter), with a survival rate of 77.25%, a feed conversion ratio (FCR) of 0.67, and a specific growth rate (SGR) of 3.28%.